2013
DOI: 10.1371/journal.pone.0065558
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modeling and In Silico Analysis of Human Superoxide Dismutase 2

Abstract: Aging in the world population has increased every year. Superoxide dismutase 2 (Mn-SOD or SOD2) protects against oxidative stress, a main factor influencing cellular longevity. Polymorphisms in SOD2 have been associated with the development of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s disease, as well as psychiatric disorders, such as schizophrenia, depression and bipolar disorder. In this study, all of the described natural variants (S10I, A16V, E66V, G76R, I82T and R156W) of SOD2 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…We next used the I-Tasser server to perform ab initio protein modeling (De Carvalho & De Mesquita, 2013;Roy, Kucukural, & Zhang, 2010;Zhang, 2008) which enabled us to construct models of both Figure 4 Structural models of Na + /K + -ATPase catalytic site in (A) E1P (Nyblom et al, 2013) and (B) E2P (Shinoda et al, 2009) conformations (PDB ID 4HQJ and 2ZXE, respectively). In both (A) and (B), color changes gradually from amino terminal (blue (dark gray in the print version)) to carboxyl terminal (red (gray in the print version)): A domain is in blue (dark gray in the print version) and cyan (light gray in the print version), P domain is in yellow (light gray in the print version), and N domain is in green (light gray in the print version).…”
Section: Deamidation Of Synaptic Proteins and Dementiamentioning
confidence: 99%
“…We next used the I-Tasser server to perform ab initio protein modeling (De Carvalho & De Mesquita, 2013;Roy, Kucukural, & Zhang, 2010;Zhang, 2008) which enabled us to construct models of both Figure 4 Structural models of Na + /K + -ATPase catalytic site in (A) E1P (Nyblom et al, 2013) and (B) E2P (Shinoda et al, 2009) conformations (PDB ID 4HQJ and 2ZXE, respectively). In both (A) and (B), color changes gradually from amino terminal (blue (dark gray in the print version)) to carboxyl terminal (red (gray in the print version)): A domain is in blue (dark gray in the print version) and cyan (light gray in the print version), P domain is in yellow (light gray in the print version), and N domain is in green (light gray in the print version).…”
Section: Deamidation Of Synaptic Proteins and Dementiamentioning
confidence: 99%
“…In this work, computational biology methods were applied, following the methodology previously described by our group [ 10 , 11 ], to an in silico analysis of hnRNPA1 protein, which has been described as the cause of familial Amyotrophic Lateral Sclerosis type 20, aiming for a thorough analysis of the protein structure and its natural variants, as well as the effects of structural changes in the disease development.…”
Section: Introductionmentioning
confidence: 99%
“…In order to combine the results of the various tools, consensus predictors have been developed to allow comparison between methods that use different analytical approaches [ 10 ] [ 31 ]. Studies using combination of different prediction tools have identified deleterious mutations in genes involved in different biological processes, including, for example, cancer (breast cancer 1, early onset— BRCA1 gene) [ 32 ], STIL gene [ 33 ], Centromere-associated protein-E gene (CENP-E) [ 34 ], leukemia (c-abl oncogene 1— ABL1 gene) [ 35 ], lipoprotein metabolism (ATP-binding cassette transporter A1— ABCA1 gene) [ 36 ], cardiomyopathy (beta myosin heavy chain— MyH7 gene) [ 28 ], oxidative stress (superoxide dismutase 2— SOD2 gene) [ 37 ], amyotrophic lateral sclerosis (superoxide dismutase 1— SOD1 gene) [ 38 ], and melanogenesis (receptor tyrosine kinase— KIT gene [ 39 ], oculocutaneous albinism type 2— OCA2 —P protein gene [ 40 ], tyrosinase— TYR gene [ 41 ], and tyrosinase-related protein 1— TYRP1 gene [ 42 ]), resulting in the establishment of the mutations with the highest pathogenic prediction.…”
Section: Introductionmentioning
confidence: 99%